The Palgrave Handbook of Volunteering, Civic Participation, and Nonprofit Associations 2016
DOI: 10.1007/978-1-137-26317-9_50
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Associations across Territories

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 168 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…In particular, the proportion focused on nonprofit management and organizations out of total theses and dissertations completed was 0.03% in 2000 but by 2013 that proportion increased to 0.16%, a fivefold increase; by 2018 it was 0.09%, still a threefold increase. Overall, this suggests that the growth in nonprofit graduate studies was faster than the increase in graduate studies overall within the same period in China, and partly mirrors the global growth reported by Smith, Never, Mohan, Prouteau, and Torpe (2016) in nonprofit studies worldwide.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In particular, the proportion focused on nonprofit management and organizations out of total theses and dissertations completed was 0.03% in 2000 but by 2013 that proportion increased to 0.16%, a fivefold increase; by 2018 it was 0.09%, still a threefold increase. Overall, this suggests that the growth in nonprofit graduate studies was faster than the increase in graduate studies overall within the same period in China, and partly mirrors the global growth reported by Smith, Never, Mohan, Prouteau, and Torpe (2016) in nonprofit studies worldwide.…”
Section: Resultssupporting
confidence: 64%
“…The regional GDP may be the most important factor, as it is known that geographic prevalence of NPOs among nations of the world or among states/provinces in a nation is substantially affected by territorial GDP (Li, 2011; Smith et al, 2016). Table 5 generally illustrates this relationship.…”
Section: Discussionmentioning
confidence: 99%